Circadian rhythms are associated with shoot architecture in natural settings. Issue 1 (19th April 2018) - Rubin, Matthew J.; Brock, Marcus T.; Baker, Robert L.; Wilcox, Stephanie; Anderson, Kyle; Davis, Seth J.; Weinig, Cynthia
Summary: Circadian rhythms are key regulators of diverse biological processes under controlled settings. Yet, the phenotypic and fitness consequences of quantitative variation in circadian rhythms remain largely unexplored in the field. As with other pathways, phenotypic characterization of circadian outputs in the field may reveal novel clock functions. Across consecutive growing seasons, we test for associations between clock variation and flowering phenology, plant size, shoot architecture, and fruit set in clock mutants and segregating progenies of Arabidopsis thaliana expressing quantitative variation in circadian rhythms. Using structural equation modeling, we find that genotypic variation in circadian rhythms within a growing season is associated directly with branching, which in turn affects fruit production. Consistent with direct associations between the clock and branching in segregating progenies, cauline branch number is lower and rosette branch number higher in a short‐period mutant relative to wild‐type and long‐period genotypes, independent of flowering time. Differences in branching arise from variation in meristem fate as well as leaf production rate before flowering and attendant increases in meristem number. Our results suggest that clock variation directly affects shoot architecture in the field, suggesting a novel clock function and means by which the clock affects performance.